Intrachromosomal recombination mediated by papovavirus large T antigens. - St-Onge, L (1990)
To investigate the mechanism by which the large T antigen (T-Ag) of polyomavirus and simian virus 40 can promote recombination in mammalian cells, we analyzed homologous recombination events occurring between two defective copies of the polyomavirus middle T (pmt) oncogene lying in close proximity on the same chromosome in a rat cell line. Reconstitution of a functional pmt gene by spontaneous recombination occurred at a rate of about 2 x 10(-7) per cell generation. Introduction of the polyomavirus large T (plt) oncogene into the cell line by DNA transfection promoted recombination very efficiently, with rates in the range of 10(-1) to 10(-2) per cell generation. Recombination was independent of any amplification of viral sequences and could even be promoted by the large T-Ag from simian virus 40, which cannot activate polyomavirus DNA replication. To explain the role of large T-Ag, we propose a novel mechanism of nonconservative recombination involving slipped-strand mispairing between the two viral repeats followed by gap repair synthesis.